GABAA receptors as novel drug targets for treatment of mental disorders - Esmaeili, Abolghasem; Ghaedi, Kamran (Archives of Advances in Biosciences, 2010)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Times; panose-1:2 2 6 3 5 4 5 2 3 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:536881799 -2147483648 8 0 511 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; font-size:12.0pt; mso-bidi-font-size:10.0pt; font-family:"Times","serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:EN-AU; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-ascii-font-family:Calibri; mso-fareast-font-family:Calibri; mso-hansi-font-family:Calibri; mso-bidi-font-family:Arial; @page Section1 size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>A balance between excitatory and inhibitory neurotransmissions in brain is an essential factor for the proper function of the brain. The amino acid gamma-aminobutyric-acid (GABA) is considered as the major inhibitory neurotransmitter in brain. Thus, GABAergic neurons play a key role in regulating behavior. Previous data have revealed the complex subunit structural design for GABAA receptor channel, in which a pentameric assembly resulting from 5 of at least 21 subunits, grouped in the eight classes alpha (α1-6), beta (β1-4), gamma (γ1-4), delta, pi (π), epsilon (ε), theta (θ) and rho (ρ1-3) permits an immense number of putative receptor isoforms. GABAARs are highly diversed in the central nervous system in which this diversity may be related to some mental disorders. Any alteration in expression of the GABAA receptor genes causes neurophysiological and functional consequences that might be associated with neurological disorders. Some neuropsychiatric disorders, such as anxiety, epilepsy and sleep disorders, are effectively treated with therapeutic agents that act on the GABAA receptor. In this article, the contribution of GABAA receptor deficits to central nervous system disorders, in particular anxiety disorders, epilepsy, schizophrenia and insomnia, will be reviewed. The better understanding of GABA and its receptors may help us to find novel therapeutic agents for treatment of mental disorder in future research.